On square root function over Qp and its application - Saburov, Mansoor; Ismai, Muhammad Jundullah (IOP Publishing, 2017)
In this paper, we introduce a square root function over the p-adic field Qp. This enables to explicitly prescribe roots of the quadratic equation over Qp. Namely, we calculate the p−adic absolute value and the first digit of roots of the quadratic equation over Qp